Community Outreach Through Police in Schools (2003) - U.S. Department of Justice, Office for Victims of Crime (My University, 2016)
This bulletin describes a collaborative effort between child development and community policing practitioners to help children cope with the effects of violence. The school-based intervention program combines the experience of police officers and mental health professionals to minimize the emotional and psychological effects of violence on middle school students. (palabras claves: comunidad, policía, escuelas, violencia infantil)